Natural post-translational modifications of chemokines. (25th October 2006) - Proost, P.; Struyf, S.; Van Damme, J.
Abstract : Chemokines, adhesion molecules, cytokines and proteases regulate the extravasation of leucocytes during acute and chronic inflammation and leucocyte homing. Chemokines are produced after transcriptional activation by inflammatory mediators such as cytokines or microbial Toll-like receptor ligands and their effect depends on the expression of chemokine receptors on specific cell types. More and more evidence points towards a role for post-translational modifications in the fine-tuning of chemokine activity. Although both glycosylation and proteolytic processing of the C- and/or N-terminus of chemokines has been reported, mainly proteolytic processing of the N-terminus appears to affect the receptor specificity, chemotactic property and signalling potency of these low-molecular-mass proteins. N-terminal processing of chemokines by aminopeptidases or endoproteases may alter the receptor specificity and may result in up- or down-regulation of their chemotactic, antiviral or angiogenic activity.